2022
DOI: 10.1136/jnnp-2022-329812
|View full text |Cite
|
Sign up to set email alerts
|

Impairments to executive function in emerging adults with Huntington disease

Abstract: Background and objectivesThe clinical diagnosis of Huntington disease (HD) is typically made once motor symptoms and chorea are evident. Recent reports highlight the onset of cognitive and psychiatric symptoms before motor manifestations. These findings support further investigations of cognitive function across the lifespan of HD sufferers.MethodsTo assess cognitive symptoms in the developing brain, we administered assessments from the National Institutes of Health Toolbox Cognitive Battery, an age-appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our study supports the evidence that cognitive changes might anticipate and predict motor progression in neurodegenerative diseases. Specifically, executive functions are documented to be impaired early in HD patients’ life 33 and are altered in several other neurological diseases. For example, SDMT does represent a critical measure in Multiple Sclerosis (MS) 34 and may predict gait impairment in this disease 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports the evidence that cognitive changes might anticipate and predict motor progression in neurodegenerative diseases. Specifically, executive functions are documented to be impaired early in HD patients’ life 33 and are altered in several other neurological diseases. For example, SDMT does represent a critical measure in Multiple Sclerosis (MS) 34 and may predict gait impairment in this disease 35 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 ] Higher numbers of CAG repeats are thought to be associated with an earlier onset of disease, a faster rate of clinical progression, and increasing disease severity. [ 11 ] Present studies show that disrupted neural circuit physiology could be found in HD mice during the first neonatal week [ 12 ] and cognitive impairments could happen earlier than the motor symptoms even in the second decades of patients, [ 13 , 14 ] which suggests the disease onset is the cumulative effect and the need for disease-modifying drugs of HD is urgent. Diagnosis of HD is typically based on clinical features, family history, and genetic testing to confirm the presence of the CAG repeat expansion in the HTT gene.…”
Section: Introductionmentioning
confidence: 99%
“…It encompasses various traditional approaches, including physical therapy, occupational therapy, speech therapy, and neuropsychology. However, the use of new rehabilitation technologies, such as virtual reality (VR), Pc-Based training, or innovative techniques, such as non-invasive brain stimulation (NIBS), could make a significant contribution to improving functional outcomes, as seen in other conditions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%